Dancers' heart: Cardiac screening in elite dancers. Issue 7 (8th August 2020) - Metsios, George S.; Wyon, Matthew; Patel, Kiran; Allen, Nick; Koutedakis, Yiannis
Abstract: Using electrocardiography and echocardiography, we screened elite men and women ballet dancers for abnormal cardiovascular conditions using an observation design with blinded clinical analysis of cardiac function tests. Fifty-eight (females n = 33) elite professional ballet dancers (age: 26.0 ± 5.7 years, body mass index: 19.9 ± 2.2 kg/m2) with no past or present history of cardiovascular disease volunteered. Participants were assessed via a 12-lead electrocardiography and two-dimensional echocardiography for cardiac function. Electrocardiography revealed that 83% of the dancers demonstrated normal axis, while 31% had incomplete right bundle branch block and 17% had sinus bradycardia; none showed any abnormal findings. Findings from the echocardiography were also normal for all participants and comparable to their counterparts in other sports. Significant differences ( p < 0.05) were detected in almost all studied echocardiographic parameters between males and females. In conclusion, heart function and structure seem to be normal in elite ballet dancers, placing them at low risk for sudden cardiac death and performance-related cardiovascular complications. Larger samples are required to confirm these findings.